Use of antenatal corticosteroids prior to preterm birth in four South East Asian countries within the SEA-ORCHID project - McDonald Steven J; Lumbiganon Pisake; Laopaiboon Malinee; Ewens Melissa R; Pattanittum Porjai; Crowther Caroline A (BMC, 2008)
Abstract Background There is strong evidence supporting the use of antenatal corticosteroids in women at risk of preterm birth to promote fetal lung maturation and reduce neonatal mortality and morbidity. This audit aimed to assess the use of antenatal corticosteroids prior to preterm birth in the nine hospitals in four South East Asian countries participating in the South East Asia Optimising Reproductive Health in Developing Countries (SEA-ORCHID) Project. Method We reviewed the medical records of 9550 women (9665 infants including 111 twins and two triplets) admitted to the labour wards of nine hospitals in four South East Asian countries during 2005. For women who gave birth before 34 weeks gestation we collected information on women's demographic and pregnancy background, the type, dose and use of corticosteroids, and key birth and infant outcomes. Results Administration of antenatal corticosteroids to women who gave birth before 34 weeks gestation varied widely between countries (9% to 73%) and also between hospitals within countries (0% to 86%). Antenatal corticosteroids were most commonly given when women were between 28 and 34 weeks gestation (80%). Overall 6% of women received repeat doses of corticosteroids. Dexamethasone was the only type of antenatal corticosteroid used. Women receiving antenatal corticosteroids compared with those not given antenatal corticosteroids were less likely to have had a previous pregnancy and to be booked for birth at the hospital and almost three times as likely to have a current multiple pregnancy. Exposed women were less likely to be induced and almost twice as likely to have a caesarean section, a primary postpartum haemorrhage and postpartum pyrexia. Infants exposed to antenatal corticosteroids compared with infants not exposed were less likely to die. Live born exposed infants were less likely to have Apgar scores of < 7 at five minutes and less likely to have any lung disease. Conclusion In this survey the use of antenatal corticosteroids prior to preterm birth varied between countries and hospitals. Evaluation of the enablers and barriers to the uptake of this effective antenatal intervention at individual hospitals is needed.